(untitled) (Jurnal Penelitian, 2016)
Pesantren is a center for the development of human values. Education in pesantren pays close attention to the potential aspects of human beings as religious creatures, namely individuals who possess the capacity to develop their abilities. This study aims to explore the implementation of education at Pesantren Syafi’i Akrom Pekalongan from the perspective of religious humanism. Field findings indicate that the learning process between teachers and students takes place through an intensive interaction pattern that upholds both human and religious values. Therefore, education at Pesantren Syafi’i Akrom can be categorized as humanistic and religious education. This is evident in the well-established human values cultivated within the pesantren environment, such as mutual respect, patience, perseverance, discipline, and tolerance, which serve as key indicators of education based on religious humanism.